(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article analyzes the structure of one of Ibn Sina’s excellent works "Al-Isharat wa al-Tanbihat" and some of his thoughts on metaphysics. Ibn Sina devotes the main philosophical concepts of the scientist to the issues of logic, physics and metaphysics. This is Ibn Sina’s greatest work written in the last years of his life. In the introduction, the author says that he begins the work with a logical presentation, then moves on to physics and considers issues related to metaphysics ( ما و التبيعة علم .